Penerapan Aturan P2TL pada Saat Dinas Jaga Laut Guna Menunjang Keselamatan Pelayaran di MV. Meratus Palembang - Saiful Rohman Firmansyah; Kuncowati Kuncowati; Nyoman Ardiana Listriawati (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
The P2TL rule is an abbreviation for the Collision Prevention Regulation at Sea, a rule that makes it easier for ships to sail safely and avoid the danger of collisions between 2 or more ships. The aim of this research is to explain the application of P2TL rules when ships are sailing to reduce the risk of collisions between ships and create safety in navigation on MV ships. Meratus Palembang. This research was carried out using quantitative descriptive statistical research methods. With data collection techniques based on the results of questionnaires, observations, literature studies related to P2TL regulations during maritime guard duty. Then the data was analyzed using SPSS calculations and described. Based on the research results, it was concluded that the P2TL rules were applied during maritime guard duty on the MV. Meratus Palembang has complied with established procedures. This is to ensure safety at sea by preventing accidents that could result in loss of life, damage to ships, and potential environmental pollution at sea.